Luminescent polypyridyl heteroleptic CrIII complexes with high quantum yields and long excited state lifetimes. Issue 39 (24th September 2020) - Jiménez, Juan-Ramón; Poncet, Maxime; Doistau, Benjamin; Besnard, Céline; Piguet, Claude
Abstract : Heteroleptic Cr III complexes combining tridentate 6-membered chelate rings: enhancing quantum yield and excited state lifetimes. Abstract : Implementing high quantum yields and long-lived excited state lifetimes within heteroleptic luminescent Cr III complexes is a keystone for the design of supramolecular energy-converting devices exploiting this cheap metal. In this contribution, we discuss the stepwise and rational optimization of these two limiting factors within a series of heteroleptic Cr III complexes.